Geographies of nature societies, environments, ecologies - Hinchliffe, Steve 1955-; SAGE Knowledge (Online service). (Los Angeles, Calif. London SAGE, 2007)
Presenting a new perspective on environmental analysis, this text argues that human ecology should be integral with our study of the natural world.
Includes bibliographical references and index.
Keywords: Human ecology; Nature -- Effect of human beings on; Human beings -- Effect of environment on; Ecosystem management; Electronic books